Can smoking duration alone replace pack-years to predict the risk of smoking-related oncogenic mutations in non-small cell lung cancer? A cross-sectional study in Japan - Masahiko Ando; Yoshihiko Taniguchi; Akihiro Tamiya; Akihide Matsumura; Koichi Ogawa; Yasuhiro Koh; Hiroyasu Kaneda; Motohiro Izumi; Yoshiya Matsumoto; Kenji Sawa; Mitsuru Fukui; Naoki Yoshimoto; et al. (BMJ Open)
Objective To investigate whether smoking duration alone can replace pack-years to predict the risk of oncogenic mutations in non-small cell lung cancer (NSCLC).Design A cross-sectional study using the baseline dataset from the Japan Molecular Epidemiology for Lung Cancer Study.Setting Forty-three medical institutions nationwide in Japan.Participants From July 2012 to December 2013, 957 patients with newly diagnosed stage I–IIIB NSCLC who underwent surgery were enrolled, and molecular analyses were performed on 876 samples (from 441 ever-smokers and 435 never-smokers).Main outcomes measured We calculated the area under the receiver operating characteristic curve (AUC) values using logistic regression to compare between the predictive values of smoking duration and pack-years for mutational frequencies in the v-Ki-ras2 Kirsten rat sarcoma (KRAS), tumour suppressor p53 (TP53), and epidermal growth factor receptor (EGFR) genes and for cytosine-to-adenine base substitution (C>A).Results For predicting KRAS mutations, the AUC values for smoking duration and pack-years were 0.746 (95% CI 0.682 to 0.800) and 0.759 (95% CI 0.700 to 0.810), respectively (p=0.058). For predicting KRAS mutations in smokers, the AUC values for smoking duration and pack-years were 0.772 (95% CI 0.697 to 0.833) and 0.787 (95% CI 0.714 to 0.845), respectively (p=0.036). There were no significant differences between the AUC values for smoking duration and pack-years in terms of predicting TP53 and EGFR mutations and C>A. Pack-years was a significantly better predictor of KRAS mutations than smoking duration.Conclusion Smoking duration was not significantly different from pack-years in predicting the likelihood of smoking-related gene mutations. Given the recall bias in obtaining smoking information, smoking duration alone should be considered for further investigation as a simpler alternative to pack-years.